UKRVO JOINT DIGITAL ARCHIVE: CURRENT STATUS AND PERSPECTIVES - Pakuliak, L.; Golovnya, V.; Virun, N.; Kazantseva, L.; Kashuba, S. (Одеські астрономічні публікації, 2013)
We discuss the current state of the UkrVO joint digital archive of photographic astronomical observations and the basic problems of its creation.